Advanced Model for Fast Assessment of Piezoelectric Micro Energy Harvesters - Ardito, Raffaele; Corigliano, Alberto; Gafforelli, Giacomo; Valzasina, Carlo; Procopio, Francesco; Zafalon, Roberto (Frontiers in Materials, 2016)
The purpose of this work is to present recent advances in modelling and design of piezoelectric energy harvesters, in the framework of Micro-Electro-Mechanical Systems (MEMS). More specifically, the case of inertial energy harvesting is considered, in the sense that the kinetic energy due to environmental vibration is transformed into electrical energy by means of piezoelectric transduction. The execution of numerical analyses is greatly important in order to predict the actual behaviour of MEMS devices and to carry out the optimization process. In the common practice, the results are obtained by means of burdensome 3D Finite Element Analyses (FEA). The case of beams could be treated by applying 1D models, which can enormously reduce the computational burden with obvious benefits in the case of repeated analyses. Unfortunately, the presence of piezoelectric coupling may entail some serious issues in view of its intrinsically three-dimensional behaviour. In this paper, a refined, yet simple, model is proposed with the objective of retaining the Euler-Bernoulli beam model, with the inclusion of effects connected to the actual three-dimensional shape of the device. The proposed model is adopted to evaluate the performances of realistic harvesters, both in the case of harmonic excitation and for impulsive loads.